Western Countries Have Shown Poorer Rather Than Better Performance Against COVID-19 - Alberto Boretti (Dr. Sulaiman Al Habib Medical Journal)
Western countries have been subjectively claimed to have performed much better than other countries in combatting COVID-19 because of their alleged democratic governance. Here, I show that the performance of their pharmaceutical and nonpharmaceutical measures has in fact been poorer than that in non-Western countries, not because of democratic governance but only because of poor decision-making.